2018
DOI: 10.1080/10408363.2018.1476455
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ethnicity on population reference values for biochemical markers

Abstract: Reference intervals (RIs) for biochemical and hematological markers determined using healthy adult and/or pediatric populations are vital for clinical interpretation of laboratory test results. Most clinical laboratories commonly use age- and sex-specific RIs, but the effect of ethnicity as a covariate is often overlooked. Ethnic differences in serum biomarker concentrations can occur as a result of genetic and environmental factors, while the degree to which each factor influences serum levels depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 123 publications
1
42
0
Order By: Relevance
“…Even in whole Chinese adult females, the upper limits of RIs for SF are also elevated. Similar findings were observed in the Canadian Health Measures Survey by Khosrow et al As mentioned above, these findings might be related to considerable variation in SF levels in ethnic origin . In fact, in multi‐ethnic population studies in the USA, Adams et al had proved that elevated SF levels are more frequent in Afro‐Caribbean and Asian subjects than in whites or Hispanics.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Even in whole Chinese adult females, the upper limits of RIs for SF are also elevated. Similar findings were observed in the Canadian Health Measures Survey by Khosrow et al As mentioned above, these findings might be related to considerable variation in SF levels in ethnic origin . In fact, in multi‐ethnic population studies in the USA, Adams et al had proved that elevated SF levels are more frequent in Afro‐Caribbean and Asian subjects than in whites or Hispanics.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, our study demon- by Khosrow et al 38 As mentioned above, these findings might be related to considerable variation in SF levels in ethnic origin. 3,22,35 In fact, in multi-ethnic population studies in the USA, Adams et al 39 had proved that elevated SF levels are more frequent in Afro-Caribbean and Asian subjects than in whites or Hispanics. In a previous Chinese study on Cobas® 6000 system E601 (Roche) analyzer, Li et al 40 also found that Chinese adult males had higher RIs for SF.…”
Section: Number Of Outliersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies find [2][3][4][5] RIs are with variety of factors involved such as race, region, ethnicity, diet, and so on. For example, Wu et al [6] found that lower limit of the platelet interval in Chinese Han adults was slightly lower than that of the peer group in the United States [7] and Malaysia [8], and RIs of white blood cell count and neutrophil count were lower than those of the homologous US population [7] while higher than those of the Africans [9]; Oliver's research [10] showed that RIs of certain biochemical indicators of the aged living in Asmara, Eritrea, were higher than those of Caucasians and lower than those of South Africans.…”
Section: Introductionmentioning
confidence: 99%